2018
DOI: 10.1038/s41467-018-06977-6
|View full text |Cite
|
Sign up to set email alerts
|

The DNA binding landscape of the maize AUXIN RESPONSE FACTOR family

Abstract: AUXIN RESPONSE FACTORS (ARFs) are plant-specific transcription factors (TFs) that couple perception of the hormone auxin to gene expression programs essential to all land plants. As with many large TF families, a key question is whether individual members determine developmental specificity by binding distinct target genes. We use DAP-seq to generate genome-wide in vitro TF:DNA interaction maps for fourteen maize ARFs from the evolutionarily conserved A and B clades. Comparative analysis reveal a high degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
178
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(183 citation statements)
references
References 72 publications
4
178
0
1
Order By: Relevance
“…Therefore, these tissue-specific accessibility maps can help drive computational-based predictions of TF binding and refine results from in vitro methods such as DNA Affinity and Purification sequencing (DAP-seq) [8,90]. Along with co-expression networks of genes from the same tissue type, the accessible chromatin maps provide a basis for strengthening TF-DNA interaction predictions.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, these tissue-specific accessibility maps can help drive computational-based predictions of TF binding and refine results from in vitro methods such as DNA Affinity and Purification sequencing (DAP-seq) [8,90]. Along with co-expression networks of genes from the same tissue type, the accessible chromatin maps provide a basis for strengthening TF-DNA interaction predictions.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, 14/15 of these significant terms were associated with "binding" activities, including protein, nucleoside, and ribonucleoside binding. Furthermore, we found these exonic DMRs were enriched at transcription factor binding sites which were identified using DAP-seq [48] (Permutation P-value < 0.001).…”
Section: Hypomethylated Regions In Maize Are Involved In Distal Gene mentioning
confidence: 93%
“…SEMs of the leaf surface showed that the epicuticular wax crystal deposition defects of ad1-ref were enhanced by the fdl1 mutation ( Figure 5D). To investigate the hypothesis that FDL1/MYB94 could directly regulate the expression of AD1 and other KCS genes, we performed DAP-seq, an in vitro DNA-TF binding assay that captures genomic DNA binding events in their native sequence context (O'Malley et al, 2016;Galli et al, 2018). In vitro expressed HALO-FDL1 proteins were incubated with maize genomic DNA libraries and FDL1bound DNA fragments were identified using next-generation sequencing.…”
Section: The Myb Transcription Factor Fused Leaves1 Positively Regulamentioning
confidence: 99%
“…Reads were mapped to the B73v3 genome as described in Galli et al, 2018(Galli et al, 2018. In brief, fastq files were trimmed using trimmomatic with the following bam Coverage with 10bp bin size and FPKM normalization.…”
Section: Dap-seq Read Mapping Filtering and Peak Callingmentioning
confidence: 99%